2014
DOI: 10.1603/en13336
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum-Specific Uv Egg Damage and Dispersal Responses in the Phytoseiid Predatory MiteNeoseiulus californicus(Acari: Phytoseiidae)

Abstract: Solar ultraviolet-B (UVB) radiation is deleterious to plant-dwelling mites. Neoseiulus californicus (McGregor) is a predominant predator of agriculturally important pest species of spider mite. However, phytoseiid mites are more vulnerable to UVB radiation than spider mites. Thus, the UVB radiation may influence decision making in foraging phytoseiid mites whether disperse or not. We tested the difference in impact and behavioral response among wavelengths of monochromatic UV radiation using a spectroscopic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Previous studies have indicated that photoperiod has a significant effect on development and reproduction of Neoseiulus barkeri [115], and harmful/harmless UV wavelength may influence decision making in foraging phytoseiid mites ( Neoseiulus californicus ) [116]. Eyeless phytoseiid mites can perceive and respond to light, including UV radiation [39].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that photoperiod has a significant effect on development and reproduction of Neoseiulus barkeri [115], and harmful/harmless UV wavelength may influence decision making in foraging phytoseiid mites ( Neoseiulus californicus ) [116]. Eyeless phytoseiid mites can perceive and respond to light, including UV radiation [39].…”
Section: Resultsmentioning
confidence: 99%
“…Second, we analyzed the peak area detected at a wavelength of 300 nm by high-performance liquid chromatography (HPLC; L-7420 UV-Vis detector; Hitachi High-Tech Science Co., Tokyo, Japan) using a reverse-phase column (6 × 100 mm, 5 µm; YMC-Pack ODS-AQ311; YMC Co., Ltd., Kyoto, Japan). UV at 300 nm and shorter wavelengths kill N. californicus eggs, whereas UV at 310 nm and longer wavelengths do not (Tachi and Osakabe, 2014). The mobile phase was eluted with a gradient from 0.1% acetic acid/15% methanol to 0.1% acetic acid/70% methanol between 0-40 min, and isocratic 0.1% acetic acid/99.9% methanol between 40-50 min.…”
Section: Uvb Absorbing Capacitymentioning
confidence: 99%
“…Tetranychus urticae and P. citri distributions, mostly on lower and upper leaf surfaces, respectively (Tachi & Osakabe, ), have been associated with their different sensitivity to UV radiation (Ohtsuka & Osakabe, ; Fukaya et al ., ; Suzuki et al ., ; Ghazy et al ., ). Therefore, differences in the time of day at which predation occurred could be related to the position of the preferred prey and/or their different UV sensitivity, such as P. persimilis being less UV sensitive than N. californicus (Tachi & Osakabe, , ; Ghazy et al ., ). Accordingly, our results show that the latter preferentially preyed early in the morning and late in the evening in summer and winter, respectively (Table ).…”
Section: Discussionmentioning
confidence: 97%